Dynamic Reliability Analysis of RV Reducer Considering Strength Degradation and Dependent Failure - Du Xuesong; Lou Jiabin; Huang Yucheng; Liu Hao (Jixie chuandong)
The strength degradation and dependent failure， which have not been taken into account yet in the existing RV reducer reliability analysis methods， have a significant impact on the reliability of mechanical systems. According to the structural characteristics of the RV reducer， a dynamic reliability analysis model with main load bearing components based on strength degradation theory is established and the rule of the effect of strength degradation on the dynamic reliability is analyzed. The Copula function is derived to describe the dependent failure among the components of the RV reducer. The dynamic reliability analysis model of RV reducer is established， the rule of the influence of the dependent failure on the RV reducer reliability is studied. The sensitivity sequence of each parameter is obtained by adopting the sensitivity analysis on the main design parameters that affecting the RV reducer reliability. The research results lay a foundation for the optimal reliability design of the RV reducer.